2011
DOI: 10.1111/j.1468-1331.2011.03501.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guidelines on the Clinical Management of Amyotrophic Lateral Sclerosis (MALS) – revised report of an EFNS task force

Abstract: Background:The evidence base for the diagnosis and management of amyotrophic lateral sclerosis (ALS) is weak. Objectives: To provide evidence-based or expert recommendations for the diagnosis and management of ALS based on a literature search and the consensus of an expert panel.Methods: All available medical reference systems were searched, and original papers, meta-analyses, review papers, book chapters and guidelines recommendations were reviewed. The final literature search was performed in February 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
606
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 935 publications
(687 citation statements)
references
References 183 publications
9
606
0
17
Order By: Relevance
“…Current interventions are limited to slowing disease progression or palliating symptoms such as dysphagia, weight loss, and respiratory muscle weakness [3,4] and the recommended interventions, such as gastrostomy and noninvasive ventilation (NIV), tend to be required by people with ALS (pwALS) in later stages of the disease [3,5]. Gastrostomy has been shown to improve nutrition, and NIV can help relieve the symptoms experienced due to diaphragmatic weakness, interventions which have improved prognosis and quality of life [6][7][8][9] without increasing caregiver burden [7].…”
Section: Introductionmentioning
confidence: 99%
“…Current interventions are limited to slowing disease progression or palliating symptoms such as dysphagia, weight loss, and respiratory muscle weakness [3,4] and the recommended interventions, such as gastrostomy and noninvasive ventilation (NIV), tend to be required by people with ALS (pwALS) in later stages of the disease [3,5]. Gastrostomy has been shown to improve nutrition, and NIV can help relieve the symptoms experienced due to diaphragmatic weakness, interventions which have improved prognosis and quality of life [6][7][8][9] without increasing caregiver burden [7].…”
Section: Introductionmentioning
confidence: 99%
“…Side effects were reported in 54% of such patients, a rate similar to that seen overall with anticholinergics. The switching and combination of anticholinergics was common place in this study, but is not well discussed in the literature and deserves further exploration [3,6,19]. It would also be useful to identify the common factors in patients who do not respond well or are intolerant to anticholinergics.…”
Section: Discussionmentioning
confidence: 99%
“…Despite remaining relatively unaddressed in many reviews and guideline articles [3,6,5,19], the use of conservative measures was often reported as part of the management for both thick and thin secretions. These are largely simple interventions which can be considered at the early stages of a secretion problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations